An in-depth review of key technologies and pathways to carbon neutrality: classification and assessment of decarbonization technologies - Zihe Wang; Yueqiao Sun; Hui Kong; Chun Xia-Bauer (Carbon Neutrality)
Abstract With the intensification of global climate change, carbon neutrality has become a crucial objective for achieving sustainable development, which critically requires systematic technological innovation and collaborative cooperation between technologies and countries. Through categorization and comprehensive technological assessments, a thorough examination of relevant technologies can furnish a framework to guide emission reduction efforts across various sectors. This review seeks to explore the methods by which various countries achieve carbon neutrality technology systems and pathways, with an in-depth study of the differences between the technological approaches and systems in China, the United States, and European countries. The construction of technology systems in several countries is reviewed, from the composition of the systems to the assessment of technologies that include indicators such as carbon reduction potential. Building upon an analysis of key technological pathways in renewable energy, carbon capture, utilization and storage, energy efficiency improvement, and hydrogen energy across different countries, a systematic evaluation is conducted from three key dimensions—policy formulation, resource endowment, and industrial foundation—to identify the similarities, differences, and driving factors in the construction of carbon neutrality technology systems among nations. Based on the previous work, we conducted a comparative analysis and summary of carbon neutrality pathways across various countries worldwide, systematically reviewing and evaluating carbon neutrality technologies in power generation, industry, transportation, and building sectors. Building upon these findings, the study offers recommendations for coupling diverse technological approaches and for international cooperation. By comparing international experiences and practices, this study provides operational references for countries in formulating technology planning and emission reduction strategies, and also provides an important basis for deepening global carbon neutral cooperation in the future.